2015
DOI: 10.1089/sur.2013.224
|View full text |Cite
|
Sign up to set email alerts
|

Positive Sterility Cultures of Transplant Solutions during Pancreatic Islet Autotransplantation Are Associated Infrequently with Clinical Infection

Abstract: In autologous islet preparations, isolation solutions frequently have positive cultures, but this finding is associated infrequently with clinical infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 28 publications
3
23
2
Order By: Relevance
“…24 Whereas prior studies have demonstrated a preponderance of gram-positive organisms such as staphylococcal, streptococcal, and enterococcal species, five of six patients with bacterial contamination also grew gram-negative bacteria, predominantly Klebsiella pneumoniae. 12,17,18 This dichotomy alone may provide a microbial milieu leading to greater β-cell death and our observed findings of lower islet yield, and higher rates of graft failure than noncontaminated patients.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…24 Whereas prior studies have demonstrated a preponderance of gram-positive organisms such as staphylococcal, streptococcal, and enterococcal species, five of six patients with bacterial contamination also grew gram-negative bacteria, predominantly Klebsiella pneumoniae. 12,17,18 This dichotomy alone may provide a microbial milieu leading to greater β-cell death and our observed findings of lower islet yield, and higher rates of graft failure than noncontaminated patients.…”
Section: Discussionmentioning
confidence: 59%
“…Prior to transplantation, established release criteria for islet products must include sterility metrics such as the absence of bacteria on Gram stain and acceptably low levels of endotoxins in the final preparation. Contamination in the pancreatic transport solution is reported as high as 61%‐68% with only 5.5%‐32.3% of final islet preparations growing bacterial contaminants after rigorous GMP isolation and antimicrobial protocols . Our rate of contaminated transportation solution was comparable at 59.3%, and contamination was substantially reduced to 22.2% in the final islet preparation with the aforementioned protocols.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Fat-soluble vitamins are provided as a water-miscible product. Bacterial contamination of the pancreas or islet product is common; it is treated with antibiotics, but conveys no adverse long-term risk when treated appropriately [31, 32]. Children are managed by a multidisciplinary team on a ward with nurses experienced in the post-operative management of TPIAT.…”
Section: Early Postoperative Carementioning
confidence: 99%